A humánerőforrás-gazdálkodás kérdései a magyar agráriumban - Horváthné Petrás, Viktória; Bertalan, Péter (Acta Scientiarum Socialium, 2019)
The aim of Human Resources Management (HR) is to efficiently handle the human resources and thereby to contribute to organizational efficiency, that is, the maintaining and increasing of the performance of an organization. HR not only provides the necessary conditions but also encourages employers to implement improvements, in accordance with their own individual, group and organizational interests, which serve the company’ goals. The economic and social changes taking place in our country have become significant factors of the efficient production in agriculture. In the current situation of the agricultural sector, the efficient use of manpower can be one of the breakout points in the future. This article provides an overview of the present situation of human resources management as well as the roles and functions it fulfils in the Hungarian agriculture.
Keywords: HR in Agriculture; Hungarian agriculture; performance appraisal